Leveraging Local Culinary Heritage as a Context for Learning Mathematics - Afandi, Rizki; Faradiba, Surya Sari; Nursit, Isbadar (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Wisnuwardhana Malang, 2025)
This study investigates how a diverse set of traditional Malang foods—including Mendol Tempe, Bakwan Malang, Tempe Chips, Cwie Mie, Rawon, Bakso Bakar, Putri Salju cookies, and Orem-Orem—can function as culturally grounded contexts for developing students’ mathematical reasoning and model-construction competencies. Each food item reveals distinct mathematical structures: density and texture patterns in Mendol Tempe, irregular yet classifiable shapes in Bakwan Malang, fractal-like crisp patterns in Tempe Chips, proportional seasoning in Cwie Mie, time-based flavor development in Rawon, rotational symmetry in Bakso Bakar, geometric uniformity in Putri Salju, and combinatorial layering in Orem-Orem. Drawing on a philosophical perspective that positions mathematics as an interpretive lens for understanding real-world phenomena, students transition from sensory observation to formal modeling, constructing representations such as ratio models, time–intensity functions, geometric similarity models, rotational interval equations, and combinatorial structures. Findings indicate that embedding mathematical tasks in local culinary culture enhances conceptual understanding, promotes creative model construction, and strengthens culturally responsive pedagogical practices. This approach highlights the natural emergence of mathematical ideas from daily life experiences, making learning more meaningful, engaging, and contextually relevant.